Electrocardiographic interpretation in athletes: the 'Seattle Criteria'. Issue 3 (9th January 2013) - Drezner, Jonathan A; Ackerman, Michael John; Anderson, Jeffrey; Ashley, Euan; Asplund, Chad A; Baggish, Aaron L; Börjesson, Mats; Cannon, Bryan C; Corrado, Domenico; DiFiori, John P; Fischbach, Peter; Froelicher, Victor; et al.
Abstract : Sudden cardiac death (SCD) is the leading cause of death in athletes during sport. Whether obtained for screening or diagnostic purposes, an ECG increases the ability to detect underlying cardiovascular conditions that may increase the risk for SCD. In most countries, there is a shortage of physician expertise in the interpretation of an athlete's ECG. A critical need exists for physician education in modern ECG interpretation that distinguishes normal physiological adaptations in athletes from abnormal findings suggestive of pathology. On 13–14 February 2012, an international group of experts in sports cardiology and sports medicine convened in Seattle, Washington, to define contemporary standards for ECG interpretation in athletes. The objective of the meeting was to develop a comprehensive training resource to help physicians distinguish normal ECG alterations in athletes from abnormal ECG findings that require additional evaluation for conditions associated with SCD.